1999
DOI: 10.7887/jcns.8.611
|View full text |Cite
|
Sign up to set email alerts
|

Intraventricular Hemorrhage caused by a Ruptured Aneurysm of the Distal Posterior Inferior Cerebellar Artery : Report of Two Cases

Abstract: We report 2 cases of ruptured aneurysms of the distal posterior inferior cerebellar artery (PICA)and review 85cases reported in the literature . Case 1 :A72 . − year − old man had headaches . Cornputed tornography (CT)revealed intraventricular hemorrhage (IVH)and hydrocephalus without subarachnoid hemorrhage (SAH) . Cerebral angiography showed an a1 ユeurysm located on the telovelo − tonsmar seglnent of the left PICA . The aneurysm ruptured again during angiography , causing the patient ' s death. Case 2 :A72 −… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…2) Cadaveric and angiographic studies have shown that the PICA arises from the extracranial portion of the vertebral artery (VA) in only 17-18% of the cases. 3,4) Some PICA aneurysms have an intradural cervical origin and are usually located in the intracranial portion.…”
Section: Introductionmentioning
confidence: 99%
“…2) Cadaveric and angiographic studies have shown that the PICA arises from the extracranial portion of the vertebral artery (VA) in only 17-18% of the cases. 3,4) Some PICA aneurysms have an intradural cervical origin and are usually located in the intracranial portion.…”
Section: Introductionmentioning
confidence: 99%